Atividade antagônica e diversidade genética de bactérias endofíticas isoladas de diferentes ciltivares de Musa spp. - Souza, Átila de (2012)
Endophytic bacteria isolated from leaf tissue of five different cultivars of banana: Maçã, Pacovan, FHIA 18, BRS Conquista and Pisangue Seilão, were considered as the genetic diversity and potential for biocontrol of fitopatogenics fungi. Of the 122 endophytics bacteria analyzed, three bacteria isolated, of Maçã cultivar and one of Pisangue Seilão submitted in vitro antagonistic activity against Colletotrichum sp. and Fusarium oxysporum f. sp. Cubense (FOC). Genetic diversity analysis was conducted using the techniques of ERIC and BOXPCR from which were obtained 35 and 26 polymorphic bands respectively. The similarity obtained by Dice coefficient varied from 1% to 100% for ERIC and 0.6% to 100% for BOX. Both markers allowed the formation of six groups, where the subgroups were composed of isolated from cultivar, demonstrating that both markers were able to correlate the isolates to the host. Using 60% of similarity as a criterion for formation of OTUs (Operational Taxonomic Units) were obtained 64 possible OTUs, indicating a large number of potential species. The data also indicate that no OTU was shared among the cultivars, which suggests a possible preference for host.